The effects of the applied tabata training model on the performance of mountain bike athletes - Aslan, I.; Yücel, O.; Toktas, H. (Kinesiologia Slovenica, 2022)
The aim of this study was to examine the development of anaerobic (maximum strength), aerobic (endurance), and heart rate numbers with the six-week Tabata Training Model applied to mountain biking athletes between the ages 14-18. A total 20 mountain bike athletes with a mean age of 15.45 ± 1.15 years participated in the study. The participants were randomly divided into two groups. The Traditional Training Group (CG) consisted of nine people and they applied the traditional training program for six weeks. The Tabata Training Group (TTG) consisted of 10 participants, and they, unlike CG, performed Tabata Interval Training on three days of the Traditional Training Program. CG did interval, rest, tempo, and endurance training for six weeks. The pre-test and post-test results showed that, aerobic power values increased by 10,7% in TTG; and 5,6% in CG, and mean power values increased by 8,6% in TTG; and 5,5% in CG. VO2max values while increased by 5,3% in TTG, it increased by 3,9% in CG, mean pulse values decreased by 0,7% in TTG and 2,8% in CG. As a result, it was seen that the Tabata Interval Model, which includes Tabata Interval Trainings applied for six weeks to high trained mountain bikers, increased the performance. In light of these results, it can be said that the Tabata Training Model is an effective training model that can be used to improve performance in high-level mountain bikers.